INTERACTION BETWEEN RECREATION ACTIVITY AND PUBLIC PREFERENCE: A CASE STUDY ON PUBLIC PARKS IN SAGA CITY, JAPAN - P. Iamtrakul; K. Teknomo; K. Hokao (Lowland Technology International, 2005)
Public parks are one of the representatives of urban environment that play an essential role to daily life of people and provide a variety of benefits and opportunities for community as green spaces. The lack of understanding of associations between pattern of park utilization and users’ preference has made difficulties to highlight the role of public parks in community while reflecting social needs of park users. To reflect actual preference of park users, Saga city in Japan was selected as a case study by employ an unconventional method to capture the real preference from actual target group of public park service. An indirect value of park users’ benefits estimation has been done through the determination of preference value factor, PVF in different users’ socioeconomic and recreation activity characteristics. The uniqueness of this method is to focus on the linkages between the availability of public parks and social preferences. On the basis of findings, the results pointed out that not only different satisfaction on park service induce on the differentiation of PVF value but the different willingness to pay on maintenance and management park service also result to demonstrates an different intuitive appreciation for environmental valuation based on park visitors’ preference.